A study on the cost of outage (electrical energy not served) in Selangor and Wilayah Persekutuan (WP) Kuala Lumpur / Norashidah Md Din, Md Zaini Jamaludin and Fatimah Ibrahim - Md Din, Norashidah; Jamaludin, Md Zaini; Ibrahim, Fatimah (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This study involves determining the cost of outages (electrical energy not served) in WP Kuala Lumpur and Selangor. The cost of outage calculations was made for Peninsular Malaysia's major electricity consumers, i.e. the residential, commercial, industrial and mining sectors. The type of outage losses for each consumer group was ascertained. A survey was conducted to obtain the necessary data for the calculations. Samples were taken from districts or mukims in WP Kuala Lumpur and Selangor based on type-of-house for the residential sector, business categories for the commercial sector, type-of-product manufactured for the industrial sector and tin mining companies in operation.